Fabrication and characterization of natural rubber/Imperata cylindricacellulose fiber biocomposites - Thulasimani, C.; Ramesh, Subramaniam; Ramesh, Kasi; Salmah, H. (Wiley, 2015)
Imperata cylindrica (IC) is one of the most abundantly found agricultural wastes that have been used to produce lignocellulose fiber and nanocellulose. Cellulose fiber from IC leaves has been isolated and characterized using Fourier transform infrared spectroscopy and scanning electron microscope. Biocomposite was prepared using Imperata cylindrica cellulose fiber (ICCF) as reinforcing filler and natural rubber (NR) as the matrix. The NR vulcanizates were cured with conventional vulcanization (CV) and efficient vulcanization (EV) curing system using two roll mills. The effect of ICCF content on curing characteristic, tensile properties, and morphology of ICCF-filled NR vulcanizates was studied. The results indicated that the tensile strength and tensile modulus of EV system were higher compared with CV system. The tensile strength and modulus at 300% increased as the ICCF content increased accompanied by a moderate decrease in elongation at break. The morphology study of biocomposites showed that ICCF were dispersed better in the NR matrix.